Greek architecture - Lawrence, A. W. (Arnold Walter), 1900-; Tomlinson, R. A. (Richard Allan) (New Haven ; London : Yale University Press, 1996)
Professor Lawrence discusses the evolution of the Hellenic age and the remaining legacy of ruins and artefacts, emphasising the continuity of their art. This edition has been revised and new illustrations have been added.
Map of Greek Mainland and Islands -- Map of Crete -- Map of the Greek World -- Diagrams of Greek Orders and Temple Plan -- pt. 1. Pre-Hellenic Building. 1. Introductory Summary. 2. Neolithic and Early Bronze Age. 3. The Beginnings of the Cretan Palaces: The Proto-Palatial Period (Middle Minoan I-II). 4. The Palace Age in Crete: The Neo-Palatial Period (Middle Minoan III -- Late Minoan). 5. Cycladic and Mainland Settlements Contemporary with Cretan Palaces (Middle and Late Bronze Age to 1400 B.C.). 6. Tholos Tombs. 7. Mycenean Citadels and Housing (Late Helladic III, 1400-1100) -- pt. 2. Hellenic Architecture. 8. Introductory Summary. 9. Primitive Temples. 10. The Doric Order. 11. Early Doric Temples and Similar Buildings. 12. The Formation of the Ionic Temple. 13. Early Fifth-Century Doric Temples and Treasuries. 14. Early Sanctuaries and the Acropolis of Athens. 15. Niceties of Doric Design. 16. Late Fifth-Century Temples except on the Acropolis. 17. Circular Buildings. 18. Temples and Tombs of 400-330. 19. Hellenistic Temples and Related Monuments. 20. Masonry, Vaulting, and Public Works. 21. Residential Buildings. 22. Town-Planning and Halls before 330. 23. Hellenistic Town-Planning and Halls. 24. Open Structures, Especially Theatres. 25. Epilogue.
Includes bibliographical references (pages 228-237) and index.
Keywords: Architecture -- Greece; Architecture, Greek; Architecture, Hellenistic